Dual in Utero Electroporation in Mice to Manipulate Two Specific Neuronal Populations in the Developing Cortex - Zhang, Longbo; Getz, Stephanie A.; Bordey, Angelique (Frontiers in Bioengineering and Biotechnology, 2022)
Precise regulation of gene expression during development in cortical neurons is essential for the establishment and maintenance of neuronal connectivity and higher-order cognition. Dual in utero electroporation provides a precise and effective tool to label and manipulate gene expression in multiple neuronal populations within a circuit in a spatially and temporally regulated manner. In addition, this technique allows for morphophysiological investigations into neuronal development and connectivity following cell-specific gene manipulations. Here, we detail the dual in utero electroporation protocol.